الأحزاب السياسية وتقييم السياسات العامة (Comprehensive Journal of Science, 2026)
Objective: This study aimed to highlight the nature of public policy which is a complex political process influenced by many variables and to demonstrate the role of political parties as key actors in planning and evaluating public policies whether in power or in opposition.Methodology: The researcher relied on the analytical approach to interpret recurring patterns in political behavior in addition to the comparative approach to identify similarities and differences in the role of political parties across legislative and executive authorities in democratic and non-democratic countries including the Arab world.Results: The results showed that political parties are among the most important parties in organized political communication gathering information and transmitting people's demands to the authority, It was also shown that the opposition plays a fundamental role in evaluating policies by exposing government mistakes and proposing alternatives while the lack of an appropriate environment in Arab countries has marginalized their role. The study concluded that public policy evaluation must be comprehensive and accompany all its stages and that political parties reflect the nature of society, recommending the necessity of activating their role in aggregating interests and advocating for participatory policies.